Psychosocial Crisis of Elizabeth Gilbert in Eat, Pray, Love - ERSYAD HAMZAH (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2016)
Abstrak Psychosocial crisis dapat dijelaskan sebagai konflik individual di masa dewasa yang meliputi hal tentang taraf hidup seseorang. Kasus ini dapat terjadi pada setiap orang seperti yang terjadi juga dalam karya sastra. Tujuan dari penelitian ini adalah untuk: (1) Mengidentifikasi krisis psikososial yang dialami Elizabeth Gilbert dalam novel Eat, Pray, Love dan (2) Menjelaskan dampak yang terjadi akibat kegagalan pada salah satu tahap perkembangan psikososial terhadap kepribadian Elizabeth Gilbert dalam novel Eat, Pray, Love. Untuk menjawab tujuan tersebut, studi menggunakan dua teori, yaitu teori psikososial oleh Erikson dan psikoseksual oleh Freud. Penelitian ini menggunakan metode kualitatif dengan metode analisis. Sumber utama studi ini adalah novel Eat, Pray, Love karangan Elizabeth Gilbert. Kumpulan data diambil dari beberapa frasa, klausa, kalimat, paragraf, dan ekspresi yang digunakan untuk memaparkan krisis psikososial yang dialami Elizabeth Gilbert sebagai karakter utama dan dampak terhadap kepribadiannya. Hasil penelitian ini menunjukkan bahwa krisis psikososial yang dialami Elizabeth Gilbert terlihat dari malignancies Gilbert pada tahap kedewasaan berdasarkan teroi perkembangan psikososial oleh Erikson. Kegagalan untuk menyelesaikan masalah pada tahap tersebut menyebabkan Gilbert menderita penyebaran dentitas yang selanjutnya berdampak pada kepribadiannya. Dia menjadi ceroboh, impulsif, putus asa, depresi, pembangkang, dan sulit untuk membuat keputusan. Kata kunci: psychosocial, psychosocial crisis, Eat, Pray, Love Abstract Psychosocial crisis is defined as personal psychosocial conflict especially in adolescence that involves confusion about one's social role and often a sense of loss of continuity to one's personality to achieve ego identity. The crisis involves a shift in perspective, requiring us to refocus our instinctual energy in accordance with the needs of each stage of the life cycle. This case may happen to any people in this world and it can lead people to do something in order to escape from their problems, such as in literary works. In Eat, Pray, Love, Elizabeth Gilbert as the main character experiences psychosocial development crisis that leads to her personality problem. This study aims to: (1) identify the psychosocial crisis of Elizabeth Gilbert in Eat, Pray, Love and (2) explain the impact of the failure in accomplishing the stage of psychosocial development toward Elizabeth Gilbert’s personality in Eat, Pray, Love. To answer the objectives, this study used both the psychosocial theory by Erikson and psychosexual theory by Freud. This study used a qualitative research with the content analysis method. The main source of this study was a novel entitled Eat, Pray, Love by Elizabeth Gilbert. The data were some phrases, clauses, sentences, paragraphs and expressions used to convey the psychosocial crisis of Elizabeth Gilbert as the main character and the impact of it to her personality. The result of this study found that a psychosocial crisis of Elizabeth Gilbert based on Erikson’s psychosocial development theory could be seen through Gilbert’s malignancies in adulthood stage: intimacy crisis and isolation. The failure to resolve the problem in that stage made her suffer from the identity diffusion that later on brough impact to her personality. She became careless, impulsive, hopeless, depression, rebellious and difficult to make decision. Keywords: psychosocial development, psychosocial crisis, Eat, Pray, Love